Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Exploring the effect of micro-pressure stewing technology on the formation of key aroma compounds in pork by means of lipidomics and lipid-derived free radical analysis - Huan Liu; Shuqi Zhao; Guofeng Jin; Pi Li; Jianjun Li; Peng Gao; Jiangtao Xing; Jianmei Zhang; Ye Zhang; Weiting Wang; Pengfei Du; Chengyu Zeng; et al. (Food Research International, 2026)

In vitro regeneration via indirect organogenesis from aseptic seedling-derived explants of the rare Tibetan medicinal shrub Sibiraea angustata - Mengting Pi; Xue Yu; Hongchang Li; Yali Guo; Wuyang Lai; Leipeng Cao; Tao Jiang; Lingxia Xu; Fuhua Peng; Hongdong Liu; Fei Wang; Jianguo Hu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Unraveling the flavor characteristics of reduced-sodium marinated duck breast prepared by potassium chloride substitute and sous-vide cooking - Siyi Zhang; Hengpeng Wang; Peng Wu; Sumin Gao; Zihan Jin; Te Pi; Yang Meng; Xiangren Meng (Food Research International, 2026)

New insight into the role of lipids in the formation and retention of key aroma compounds in micro-pressure stewed beef based on lipidomics and lipid-derived free radical analysis - Huan Liu; Yu Liu; Xinhe Zhang; Bo Xiao; Pi Li; Peng Gao; Jiangtao Xing; Weiting Wang; Pengfei Du; Jingxian Cong; Chengyu Zeng; Cheng Li; et al. (Food Research International, 2026)

Oleophobic/hydrophobic microporous polystyrene-based foam with thermally stable wettability for high-temperature W/O emulsion separation - Yunpeng Zhang; Yunjia Wang; Yajuan Peng; Shouping Xu; Xiufang Wen; Zehao Chen; Pihui Pi (Chemical Engineering Journal, 2026)

Bioinspired self-assembled gradient Janus bilayer aerogel enabling coupled solar desalination and purification of multicomponent oily emulsions - Peng Pi; Yu Feng; Wen Jung Li; Ling Pan; Youxi Lin; Linxi Hou; Zihao Huang; Qinwei Wang; Xuhui Wang; Zhiying Ren (Chemical Engineering Journal, 2026)

Research progress on the characteristics of milk allergens and the effect of Maillard reaction and its assistance treatment on allergenicity - Xiaowen Pi; Tanying Zhang; Jia Cao; Zeyu Peng; Bowen Li; Haozhe Yi; Wanxiang Guo; Jing Che; Chen Wang; Jinshen Chu (Food Chemistry, 2026)

The inhibition of the AMPK and PPAR signaling pathways may be involved in the metabolic disorder of large yellow croaker induced by Pseudomonas plecoglossicida ppTse6 - Huan-jiao Tan; Yu-jia Sun; Xi-zhi Peng; Qing-pi Yan (Fish & Shellfish Immunology, 2026)

A review of tree nut allergens and their processing for decreasing allergenicity - Haochen Ye; Tanying Zhang; Siyu Ren; Jingwei Jiang; Zeyu Peng; Jia Cao; Jinshen Chu; Bowen Li; Haozhe Yi; Binjia Zhang; Huan Wang; Xiaowen Pi (Trends in Food Science & Technology, 2026)

Structural characteristics and oxidative stability of diacylglycerols prepared from Huajiao seed oil - Xiaowei Peng; Chi Zhang; Ting Wang; Yan Pi; Jianquan Kan (Food Chemistry, 2026)

Boosting the built-in electric field via sulfur vacancy engineering in an g-C3N4@FeS2 Z-scheme heterojunction for TC photocatalytic degradation: Process, mechanism and application - Yue Zhou; Xianbin Hu; Fangfang Zhao; Yiren Pi; Xiaoming Peng; Zhen Huang; Xing Xu; Peng Zhan; Caihua Liu; Junhui Zhou (Chemical Engineering Journal, 2026)

Slab kinematics and strain localization in NE China: Polyphase deformation of the Hulin Complex during Late Mesozoic subduction - Wei Pi; Han Zheng; Jian Zhang; Zhiyuan He; Johan De Grave; Ian P. Cawood; Yong Liang; Heng Peng; Guochun Zhao (Journal of Structural Geology, 2026)

The formation, characteristic, and stability of oat protein-hyaluronic acid complexes on perilla oil emulsion and its application in plant-based mayonnaise - Xiaowen Pi; Zhenling Chen; Chunyan Bo; Jinshen Chu; Zeyu Peng; Jia Cao (Food Chemistry, 2026)

Cadmium Exposure Facilitates Oral Squamous Cell Carcinoma Progression and Epithelial–mesenchymal Transition Through the Upregulation of ATP1B4 - Jianbo Zhang; Jingdian Li; Jinghong Liu; Yongchun Peng; Huifeng Pi; Weijia Qing; Zhijing He; Xi Zhou; Bo Li; Junxin Liu; Qingyun Lin; Tengfei Fan (Biological Trace Element Research, 2026)

Maternal exposure to indoor and outdoor air pollution during pregnancy increases offspring risk of autism spectrum disorder - Lingxi Wang; Wei Li; Yunchong Yao; Xiufang Jiang; Dongmei Ma; Yinxia Liu; Yunhua Deng; Lijiao Sun; Hong Li; Yuping Zhao; Guangyang Peng; Guo Wei; et al. (Environmental Research, 2026)

Leveraging Mn(II)/UV/oxalic acid synergy for efficient and green Cr(VI) removal: Promoted Mn(II)/Mn(III) redox cycling and •CO₂− radical generation - Peng Xu; Changchao Pi; Jingwei Ma; Qiulai He; Mengqi Zheng; Jing Zou; John C. Crittenden (Chemical Engineering Journal, 2026)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Corrigendum to “Impact of ultrasound on food allergenicity: A review of current research and future perspective” [Food Res. Int. 221 (2025) 117424] - Zeyu Peng; Guohui Xue; Zhenling Chen; Jia Cao; Jinshen Chu; Xiaowen Pi (Food Research International, 2025)

New insight into the formation mechanism of key aroma compounds in the micro-pressure stewed duck meat: A volatilomics and lipidomics-based approach - Lei Zhao; Lin Li; Pi Li; Peng Gao; Jiangtao Xing; Chengyu Zeng; Cheng Li; Wanmei Wu; Daohong Zhang; Huan Liu (Food Research International, 2025)

Impact of ultrasound on food allergenicity: A review of current research and future perspective - Zeyu Peng; Guohui Xue; Zhenling Chen; Jia Cao; Jinshen Chu; Xiaowen Pi (Food Research International, 2025)

Structural characterization of almond polysaccharides (Armeniaca Sibirica L. Lam) and the prebiotic effects on human intestinal flora - Yanqi Peng; Ji Wu; Mingyue Ma; Yuzhen Pi; Xiqing Yue; Yanyu Peng (Food Chemistry, 2025)

The impact of hydrological regime changes induced by run-of-river hydroelectric stations on fish spawning - Jing Zhang; Wu Sha Ji Pi; Zi Jing Chen; Shi-Tao Peng; Bing Xing; Tao Lan; Er Di A Bi (Ecohydrology & Hydrobiology, 2025)

Impact of batch selenium on Spirulina platensis: growth, enrichment, and metabolism - Yue Zhou; Bin Li; Zhenghua Huang; Fuhua Peng; Mengting Pi; Yajie Xiao; Lili He; Leipeng Cao (Algal Research, 2025)

Mn(II) strengthens UV irradiation-induced Cr(VI) photocatalysis: enhanced Cr(VI) activation-regeneration cycle and non-radical mediated tetracycline degradation - Jiaxin Miao; Peng Xu; Jingwei Ma; Changchao Pi; Xufeng He; Yuxi Wu; Baolin Hou (Chemical Engineering Journal, 2025)

Exploring the freshness biomarker and volatiles formation in stored pork by means of lipidomics and volatilomics - Yuping Zhang; Jingyu Li; Zixu Zeng; Xiangru Wei; Nigel P. Brunton; Yanqing Yang; Peng Gao; Jiangtao Xing; Pi Li; Fangjie Liu; Rui Liu; Qianqian Li; et al. (Food Research International, 2025)

A lipidomic and volatilomic approach to map the lipid profile and related volatile compounds in roasted quail meat using circulating non-fried roast technology - Huan Liu; Yuping Zhang; Hengbin Ji; Junke Li; Qianli Ma; Nazimah Hamid; Jiangtao Xing; Peng Gao; Pi Li; Jianxun Li; Qianqian Li (Food Chemistry, 2024)

Formation and retention of aroma compounds in pigeons roasted by circulating non-fried roast technique by means of UHPLC-HRMS and GC-O-MS - Huan Liu; Jingyu Li; Yuping Zhang; Lin Li; Hansheng Gong; Lixuan Tan; Peng Gao; Pi Li; Jiangtao Xing; Bin Liang; Jianxun Li (Food Chemistry, 2024)

Unraveling the formation mechanism of aroma compounds in pork during air frying using UHPLC-HRMS and Orbitrap Exploris GC–MS - Jingyu Li; Yuping Zhang; Renyu Zhang; Rujie Yang; Qianli Ma; Zhongshuai Wang; Pi Li; Jiangtao Xing; Peng Gao; Huan Liu; Hansheng Gong (Food Research International, 2024)

Polyphenol (−)-Epigallocatechin Gallate (EGCG) mitigated kidney injury by regulating metabolic homeostasis and mitochondrial dynamics involvement with Drp1-mediated mitochondrial fission in mice - Yue-Lei Chu; Jin-Chan Pi; Yu-Fei Yao; Xuan-Ying Chen; Xiao-Ping Peng; Wen-Juan Li (Food and Chemical Toxicology, 2024)

A dynamic multi-objective optimization evolutionary algorithm with adaptive boosting - Hu Peng; Jianpeng Xiong; Chen Pi; Xinyu Zhou; Zhijian Wu (Swarm and Evolutionary Computation, 2024)

Sesame allergy: mechanisms, prevalence, allergens, residue detection, effects of processing and cross-reactivity - Xiaowen Pi; Zeyu Peng; Jiafei Liu; Yunqing Jiang; Jiarong Wang; Guiming Fu; Yili Yang; Yuxue Sun (Critical Reviews in Food Science and Nutrition, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Distinct toxic effects, gene expression profiles, and phytohormone responses of Polygonatum cyrtonema exposed to two different antibiotics - Guoqun Yang; Dong Jiang; Li-Jun Huang; Chuantong Cui; Runke Yang; Xin Pi; Xia Peng; Xiaofeng Peng; Jianhui Pi; Ning Li (Journal of Hazardous Materials, 2024)

Unveiling the toxic effects, physiological responses and molecular mechanisms of tobacco (Nicotiana tabacum) in exposure to organic ultraviolet filters - Dong Jiang; Guoqun Yang; Li-Jun Huang; Kebin Chen; Yangcan Tang; Xin Pi; Runke Yang; Xia Peng; Chuantong Cui; Ning Li (Journal of Hazardous Materials, 2024)

Characteristics of ash formed by different lubricant additives and its effect on DPF performance - Pi-qiang Tan; Tian-peng Liu; Li-shuang Duan; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

Solution chemistry strategies to construct a stable MAPbI3 film toward high performance of amplified spontaneous emission - Haoyue Luo; Mingyu Pi; Zijun Zhan; Nian Liu; Xin Zeng; Jie Zeng; Yuan Xiang; Xinyi Kuang; Yexiong Huang; Juan Du; Dingke Zhang; Zhengzheng Liu; et al. (Chemical Engineering Journal, 2024)

Effects of lubricant components on ash-bridge deposition characteristics in the diesel particulate filter - Pi-qiang Tan; Yuan Tian; Li-shuang Duan; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

Exploring the formation and retention of aroma compounds in ready-to-eat roasted pork from four thermal methods: A lipidomics and heat transfer analysis - Huan Liu; Qianli Ma; Jiangtao Xing; Pi Li; Peng Gao; Nazimah Hamid; Zhongshuai Wang; Ping Wang; Hansheng Gong (Food Chemistry, 2024)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Physicochemical characteristics of ash-bridges in diesel particulate filter - Li-shuang Duan; Pi-qiang Tan; Yun-peng Li; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

Effect of ash on temperature and particulate emission characteristics of diesel particulate filter during active regeneration - Li-shuang Duan; Pi-qiang Tan; Yi-fan Yin; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

Understanding the role of lipids in aroma formation of circulating non-fried roasted chicken using UHPLC-HRMS-based lipidomics and heat transfer analysis - Huan Liu; Dengyong Liu; Raheel Suleman; Peng Gao; Pi Li; Jiangtao Xing; Qianli Ma; Nazimah Hamid; Ping Wang; Hansheng Gong (Food Research International, 2023)

Priority control factors for heavy metal groundwater contamination in peninsula regions based on source-oriented health risk assessment - Yujie Pan; Hongxia Peng; Qingqin Hou; Ke Peng; Huanhuan Shi; Simiao Wang; Wuhuan Zhang; Min Zeng; Changsheng Huang; Letian Xu; Pengcheng Pi (Science of The Total Environment, 2023)

Identification of Molecular Markers for Fertility in Sugar Beet - Fei Peng; Shengnan Li; Zhi Pi; Zedong Wu (Sugar Tech, 2023)

Heterojunction Mo-based binary and ternary nitride catalysts with Pt-like activity for the hydrogen evolution reaction - Xueling Wang; Xuming Zhang; Yifan Xu; Hao Song; Xingrui Min; Zihuan Tang; Chaoran Pi; Jianping Li; Biao Gao; Yang Zheng; Xiang Peng; Paul K. Chu; et al. (Chemical Engineering Journal, 2023)

Ultra-rapid and long-lasting activation of peracetic acid by Cu-Co spinel oxides for eliminating organic contamination: Role of radical and non-radical catalytic oxidation - Peng Shen; Kunjie Hou; Fei Chen; Zhoujie Pi; Li He; Shengjie Chen; Xiaoming Li; Qi Yang (Chemical Engineering Journal, 2023)

LncRNA-UC.25 + shRNA Alleviates P2Y14 Receptor–Mediated Diabetic Neuropathic Pain via STAT1 - Baoguo Wu; Congfa Zhou; Zehao Xiao; Gan Tang; Hongmin Guo; Zihui Hu; Qixing Hu; Hao Peng; Lingzhi Pi; Zhihua Zhang; Miaomiao Wang; Taotao Peng; et al. (Molecular Neurobiology, 2022)

Biopharmaceutics Applications of Physiologically Based Pharmacokinetic Absorption Modeling and Simulation in Regulatory Submissions to the U.S. Food and Drug Administration for New Drugs - Fang Wu; Heta Shah; Min Li; Peng Duan; Ping Zhao; Sandra Suarez; Kimberly Raines; Yang Zhao; Meng Wang; Ho-pi Lin; John Duan; Lawrence Yu; et al. (The AAPS Journal, 2021)

Construction of a new plant expression vector and the development of maize germplasm expressing the Aspergillus ficuum phytase gene PhyA2 - Peng Jiao; Wen-Ya Yuan; Han-Dan Zhao; Jing Qu; Pi-Wu Wang; Shu-Yan Guan; Yi-Yong Ma (Genetic Resources and Crop Evolution, 2021)
Phytases, which belong to a special category of orthophosphoric monoester phosphohydrolases, degrade inositol hexaphosphate to produce lower-grade inositol phosphate derivatives and inorganic phosphate. Thus, phytases may improve phosphorus utilization, eliminate the anti-nutrient properties of phytic acid, and mitigate environmental pollution due to phosphorus contamination. In this study, we constructed a new root-specific expression vector by inserting the Aspergillus ficuum phytase gene PhyA2 into pCAMBIA3301-ZmGLU1P-Nos. The subsequent molecular analysis confirmed that six T 4 generation transgenic plants carried and expressed PhyA2 . A quantitative real-time PCR analysis indicated PhyA2 was highly expressed in the transgenic roots. Additionally, the phytase activity was 10.9-fold higher in the transgenic roots (peak activity of 5.432 U/g) than in the control roots. Moreover, compared with the control rhizosphere, the organic phosphorus content in the rhizosphere of the transgenic plants decreased significantly (by up to 5.21 mg/kg). An agronomic trait analysis indicated that PhyA2 expression can increase maize seed weight by up to 25.8 g. Therefore, the integration of PhyA2 into the maize genome can enhance the ability of maize plants to use the phosphorus compounds in soil, while also improving the plant growth status and increasing the seed yield.

Correlation of exosomal microRNA clusters with bone metastasis in non-small cell lung cancer - Xiao-Rong Yang; Can Pi; Ruoying Yu; Xiao-Jun Fan; Xiao-Xiao Peng; Xu-Chao Zhang; Zhi-Hong Chen; Xue Wu; Yang Shao; Yi-Long Wu; Qing Zhou (Clinical & Experimental Metastasis, 2021)
20–40% of lung cancer patients develop bone metastasis (BM) with significantly decreased overall survival. Currently, BM is mainly diagnosed by computerized tomography (CT) scan or magnetic resonance imaging (MRI) when symptom develops. Novel biomarkers with higher prediction value of BM are needed. Plasma-derived exosomal microRNAs had been isolated and sequenced of total 30 non-small cell lung cancer (NSCLC) patients including 16 with bone metastasis and 14 without bone metastasis. Hierarchical clustering based on the total miRNA profile can clearly separate cancer patients and healthy individuals (H), but not patients with (BM +) or without (BM−) BM. Weight Co-expression network of miRNAs (WGCNA) analyses identified three consensus clusters (A, B, C) of highly correlated miRNAs, among which cluster B (144 miRNAs) showed significantly differential expression in lung cancer patients, especially in BM + group. Pathway analysis of cluster B miRNAs revealed enrichment in metabolic pathways that may involve in preconditioning of the metastatic niche. Three differentially expressed miRNAs between BM + and BM− patients within cluster B were identified as miR-574-5p, a suppressor of Wnt/β-catenin pathway, was down-regulated, while miR-328-3p and miR-423-3p, two activators of the same pathway, were up-regulated in BM + patients. Cluster A miRNAs (n = 49) also showed trend of upregulation in BM + patients. Interestingly, pathway analysis indicated that 43 of them are associated with chromosome14, which has been suggested to promote epithelial-mesenchymal transition (EMT) and bone metastasis.

Chinese public participation monitoring and warning system for geological hazards - Sheng-nan Wu; Yu Lei; Peng Cui; Rong Chen; Pi-hua Yin (Journal of Mountain Science, 2020)

Gender differences and lung cancer risk in occupational chefs: analyzing more than 350,000 chefs in Taiwan, 1984–2011 - Pei-Chen Lin; Chiung-Yu Peng; Chih-Hong Pan; Pi-I Debby Lin; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2019)

Fluid evolution and ore genesis of the Dalingshang deposit, Dahutang W-Cu ore field, northern Jiangxi Province, South China - Ning-Jun Peng; Shao-Yong Jiang; Suo-Fei Xiong; Dao-Hui Pi (Mineralium Deposita, 2018)

The effects of El Niño‐Southern Oscillation events on intertidal seagrass beds over a long‐term timescale - Hsing‐Juh Lin; Chen‐Lu Lee; Shang‐En Peng; Meng‐Chi Hung; Pi‐Jen Liu; Anderson B. Mayfield (Global Change Biology, 2018)
El Niño‐Southern Oscillation (ENSO) events can cause dramatic changes in marine communities. However, we know little as to how ENSO events affect tropical seagrass beds over decadal timescales. Therefore, a diverse array of seagrass ( Thalassia hemprichii ) habitat types were surveyed once every 3 months for 16 years (January 2001 to February 2017) in a tropical intertidal zone that is regularly affected by both ENSO events and anthropogenic nutrient enrichment. La Niña and El Niño events had distinct effects on the biomass and growth of T. hemprichii . During La Niña years, higher (a) precipitation levels and (b) seawater nitrogen concentrations led to increases in seagrass leaf productivity, canopy height, and biomass. However, the latter simultaneously stimulated the growth of periphyton on seagrass leaves; this led to decreases in seagrass cover and shoot density. More frequent La Niña events could, then, eventually lead to either a decline in intertidal seagrass beds or a shift to another, less drought‐resistant seagrass species in those regions already characterized by eutrophication due to local anthropogenic activity.

Mass spectrometry-guided isolation of two new dihydrobenzophenanthridine alkaloids from Macleaya cordata - Zhi-Xing Qing; Peng Yang; Kun Yu; Xue-Yi Yang; Jing-Hong Liu; Feng Xiang; Hua-Liang Cao; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2017)

Mass spectrometry-guided isolation of two new benzoquinoline alkaloids from Macleaya cordata - Zhi-Xing Qing; Yu-Qin Xu; Peng Yang; Kun Yu; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2016)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Taxonomic treatments of Camellia (Theaceae) species with secretory structures based on integrated leaf characters - B. Jiang; Q. F. Peng; Z. G. Shen; M. Möller; E. X. Pi; H. F. Lu (Plant Systematics and Evolution, 2010)

Preliminary proteomic analysis of circulating polymorphonuclear neutrophils from rabbits experiencing scald injury and Staphylococcus aureus sepsis - Pi-hong Zhang; Li-li Li; Ji-zhang Zeng; Liu-rong Yang; Li-cheng Ren; Peng-fei Liang; Xiao-Yuan Huang (Inflammation Research, 2010)

Sample digestion for determining chloramphenicol residues in carp serum and muscle - Zhi-Yong Huang; Qing-Pi Yan; Qiang Zhang; Ai-Hong Peng (Aquaculture International, 2009)

Protection effect of piper betel leaf extract against carbon tetrachloride-induced liver fibrosis in rats - Shun-Chieh Young; Chau-Jong Wang; Jing-Jing Lin; Pei-Ling Peng; Jui-Ling Hsu; Fen-Pi Chou (Archives of Toxicology, 2007)